2019
DOI: 10.1094/pdis-02-19-0298-re
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Against Melon Chlorotic Mosaic Virus and Tomato Leaf Curl New Delhi Virus in Melon

Abstract: Thirty-one melon accessions were screened for resistance to the begomoviruses Melon chlorotic mosaic virus (MeCMV) and Tomato leaf curl New Delhi virus (ToLCNDV). Five accessions presented nearly complete resistance to both viruses. Accession IC-274014, showing the highest level of resistance to both viruses, was crossed with the susceptible cultivar Védrantais. The F1, F2, F3/F4, and both backcross progenies were mechanically inoculated with MeCMV. Plants without symptoms or virus detection by enzyme-linked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…The symptoms were similar to those of Tomato leaf curl New Delhi virus (ToLCNDV), an emerging bipartite begomovirus affecting cucurbits in the Mediterranean Basin (Fortes et al ., 2016). After DNA extraction, PCR was performed on a symptomatic sample (CD20001) with specific primers TLCNDV‐CP‐5 and TLCNDV‐CP‐3, and ToLCNDV‐B‐900‐5 and ToLCNDV‐B‐1940‐3 (Romay et al ., 2019) targeting ToLCNDV DNA‐A and DNA‐B respectively. The amplified fragments (760 bp and 1072 bp) displayed 99.1% and 99.6% identity respectively to ToLCNDV isolate MU.12.ZU/1/2 (MH577761) from Spain.…”
Section: Figurementioning
confidence: 99%
“…The symptoms were similar to those of Tomato leaf curl New Delhi virus (ToLCNDV), an emerging bipartite begomovirus affecting cucurbits in the Mediterranean Basin (Fortes et al ., 2016). After DNA extraction, PCR was performed on a symptomatic sample (CD20001) with specific primers TLCNDV‐CP‐5 and TLCNDV‐CP‐3, and ToLCNDV‐B‐900‐5 and ToLCNDV‐B‐1940‐3 (Romay et al ., 2019) targeting ToLCNDV DNA‐A and DNA‐B respectively. The amplified fragments (760 bp and 1072 bp) displayed 99.1% and 99.6% identity respectively to ToLCNDV isolate MU.12.ZU/1/2 (MH577761) from Spain.…”
Section: Figurementioning
confidence: 99%
“…In fact, in melon, besides the major QTL of chromosome 11, two additional minor regions in chromosomes 12 and 2 modifying the resistant response were identified (Sáez et al, 2017). In a recent publication (Romay et al, 2019), one recessive (bgm-1) and two dominant (Bgm-2 and Tolcndv) genes were also found controlling resistance to ToLCNDV in the same Indian accession WM-7. A similar oligogenic control, three dominant genes, has been reported in S. habrochaites S. Knapp & D. M. Spooner, a wild species related to tomato, after ToLCNDV agroinoculation (Rai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In melon, a major locus in chromosome 11 and two additional regions in chromosomes 2 and 12 controlling the resistance of the wild agrestis accession WM-7 were found [ 24 ]. In a recent publication, Romay et al [ 55 ] identified in the same Indian accession WM-7 one recessive ( bgm-1 ) and two dominant ( Bgm-2 and Tolcndv ) genes controlling the resistance to ToLCNDV. In Cucurbita moschata , a major recessive gene located in chromosome 8 was found controlling the resistance in an Indian accession.…”
Section: Discussionmentioning
confidence: 99%